The Influence of the Use of Interactive Digital Media in Sewing Pattern Activities on Students' Cognitive Aspects and Mathematical Abilities - Ahmed, Muhammedalameen; Darmayanti, Rani; Purnamasari, Purnamasari (Delta-Phi: Jurnal Pendidikan Matematika, 2024)
-Cognitive abilities are critical for children to develop knowledge through sensory experiences. This study aims to determine the effect of the use of interactive digital media in sewing pattern activities on the cognitive development and creativity of children in Group B at Idhata Bucinri Kindergarten, Pangkajene Regency. This study used a quasi-experimental method with a pretest-posttest control group design. The subjects of the study were 17 children in Group B, where each child had an equal opportunity to participate in this activity, such as in the concept of probability. The children were divided into two groups: an experimental group that used interactive digital media as a sewing guide, and a control group that used conventional methods. The study was conducted for 10 days, with cognitive and creative aspects measured before and after treatment. The results showed that the group that used interactive digital media experienced a significant increase in cognitive and creative aspects compared to the control group. This increase can be expressed as asignificant difference between the averages of the two groups. The use of interactive digital media as media content in sewing pattern activities has proven effective in supporting students' cognitive development.